2000
DOI: 10.1128/mcb.20.23.9076-9083.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and Structural Analyses of the Ribonucleotide Reductase Inhibitor Sml1 Define Its Rnr1 Interaction Domain Whose Inactivation Allows Suppression of mec1 andrad53 Lethality

Abstract: In budding yeast, MEC1 and RAD53 are essential for cell growth. Previously we reported that mec1 or rad53 lethality is suppressed by removal of Sml1, a protein that binds to the large subunit of ribonucleotide reductase (Rnr1) and inhibits RNR activity. To understand further the relationship between this suppression and the Sml1-Rnr1 interaction, we randomly mutagenized the SML1 open reading frame. Seven mutations were identified that did not affect protein expression levels but relieved mec1 and rad53 inviabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 36 publications
11
102
0
Order By: Relevance
“…1A and B). Residues 28 to 50 of Sml1 were predicted to be a nonstructural linker region between the N-and C-terminal alpha-helical regions of the protein; removal of this region does not affect Sml1's inhibition of RNR activity (53). We found that removal of residues 28 to 50 in Sml1 greatly increased stability of the protein both in cells under normal growth conditions and in cells treated with HU and MMS (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…1A and B). Residues 28 to 50 of Sml1 were predicted to be a nonstructural linker region between the N-and C-terminal alpha-helical regions of the protein; removal of this region does not affect Sml1's inhibition of RNR activity (53). We found that removal of residues 28 to 50 in Sml1 greatly increased stability of the protein both in cells under normal growth conditions and in cells treated with HU and MMS (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Sml1 is an unstable protein and undergoes checkpoint-dependent phosphorylation and degradation during S phase of the cell cycle and in cells experiencing genotoxic stress (52,55). Although no apparent sequence homolog of Sml1 has been identified in multicellular organisms, Sml1 can bind the mammalian R1 and inhibits its activity (8,53), suggesting a conserved mechanism of Sml1-R1 interaction and inhibition.…”
mentioning
confidence: 99%
“…At present, there are three mechanisms proposed to regulate RNR activity. One involves the small protein Sml1 that binds to α and causes inhibition by a poorly understood mechanism (74,78,79). The second is feedback inhibition by dATP.…”
Section: Specific Activity Measurements Suggest That Rnr Need Not Be mentioning
confidence: 99%
“…Measurement of the frequency of petite formation and the two-hybrid assay method has been described (3). Cell cycle arrest, fluorescence-activated cell sorting, genotoxin treatment, extraction of yeast proteins, and protein blot analysis have been described (5,19). The IMAGEQUANT program (Molecular Dynamics) was applied to measure the density of bands on protein blots.…”
Section: Dun1mentioning
confidence: 99%